(untitled) (Annals of Medical Research, 2021)
Aim: This study was planned with the hypothesis that atherosclerosis is in the etiology of peripheral artery disease (PAD), whether symptomatic or not, and therefore thrombocyte-related parameters could show variability.Material and Methods: A retrospective examination was made of the laboratory records of 48 patients who presented at the Cardiovascular Surgery Polyclinic with mild or severe symptoms and were diagnosed with PAD and a control group of 33 healthy individuals.Results: No difference was determined between the patient and control groups in respect of age, gender, Platelet Count (Plt), C-reactive protein (CRP), neutrophil-lymphocyte ratio (NLR), Mean Platelet Volume ( MPV), Hemoglobin (Hgb) and White Blood Cells (WBC ) values. The Platelet distribution width (PDW) value of the patient group was found to be statistically significantly higher than that of the control group (p0.05). PDW was determined with high sensitivity (58.3%) and specificity 861%) for PAD. Conclusion: In an individual developing PAD, the onset of the atherosclerotic process in the vascular structure is a warning. According to the data obtained in this study, elevated PDW can be used as a marker that the atherosclerotic process has started in the vascular structure.